ALFALFA DISEASES AND CONCEPTUAL FOUNDATIONS OF PROTECTION IN THE EASTERN FOREST-STEPPE OF UKRAINE - Turenko В.; Horiainova В.; Zhukova Л. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The article presents the research results on the studies of spreading, harmfulness, biological characteristics of alfalfa fungal disease pathogens in the Eastern Forest-Steppe of Ukraine. Monitoring of alfalfa diseases showed that brown spot (Pseudopeziza medicaginis (Lib Sace)), down mildew (Peronospora aestivalis Sya.), Ascochitosis (Ascochyta imperfecta Peck.) and yellow spot were the most harmful (Pseudopeziza yonesii Nann.). The relationship between the indicators of the maximum spreading and development of diseases and meteorological factors during crop vegetation was confirmed. The screening to reveal the resistance of promising alfalfa varieties to the disease was carried out showing that Vlasta and Unitra varieties were characterized by group resistance to fungal diseases. The high efficiency of summer wide-row crops use in stabilization the phytosanitary state was found to ensure a decrease of major alfalfa diseases spreading by 11.8–17.5 % as compared with row crops. The necessity of stubble combing out early in spring was proved. It helps reducing the infection stock in crops and disease spreading during the alfalfa vegetation period by 1.0–2.4 %, their development by 1.6–2.8 % as compared to the control. Equations have been developed to predict the maximum prevalence of alfalfa Ascochytosis У1 = 0.034×9.651 and its maximum development У2 = 0.025x+3.9. The data use of our short-term forecast as to alfalfa disease development enables spray alfalfa in the budding phase with 25 % e.c. of Тilt at a rate of 0.5 l/ha and sulfate zinc 0.02 kg/ha in the proper time. At the same time, the spreading of fungal diseases decreased by 3.6 %, the development of diseases – by 1.3 %, as compared with the conventional technology of alfalfa growing.